2017
DOI: 10.1063/1.4973935
|View full text |Cite
|
Sign up to set email alerts
|

Metabasin transitions are Johari-Goldstein relaxation events

Abstract: We show that by representing quasi-elastic and inelastic neutron scattering from propylene carbonate (PC) with an explicitly heterogeneous model, we recover signatures of two distinct localized modes in addition to diffusive motion. The intermediate scattering function provides access to the time-dependence of these two localized dynamic processes, and they appear to correspond to transitions between inherent states and between metabasins on a potential energy landscape. By fitting the full q-dependence of ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 62 publications
4
26
0
Order By: Relevance
“…5(a)). This is consistent with the recent neutron scattering results on propylene carbonate 19 . In addition, and as for the molecular rotations, a fraction of rearrangements will be characterized by a much longer length-scale.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5(a)). This is consistent with the recent neutron scattering results on propylene carbonate 19 . In addition, and as for the molecular rotations, a fraction of rearrangements will be characterized by a much longer length-scale.…”
Section: Discussionsupporting
confidence: 93%
“…Nuclear γ -resonance time-domain interferometry (TDI) experiments on PB 16 and on the molecular glass-former o-terphenyl (OTP) 11,17 confirm the existence of the β JG relaxation at the intra-molecular scale, and demonstrate for OTP that it corresponds to a restricted dynamics 11,17 . More recent incoherent elastic and inelastic neutron scattering experiments on propylene carbonate analysed using an heterogeneous dynamics model suggest that the β JG relaxation is characterized by a mean square displacement of about 0.5 Å and should therefore be associated to metabasin transitions in a potential energy landscape description of the undercooled liquid 19 . It would be important to generalize this conclusion to more glass-formers and, possibly, using experimental schemes requiring less, or at least different, model hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…This is a curious possibility that would naturally explain the observed decoupling relation between ⌧ ↵ and t ⇤ found in previous simulation studies. 37,53 This relationship would also be consistent with the string motions corresponding to intrabasin inherent transition events, 91 while the stringlets would then reflect intrabasin motions within the potential energy landscape. This scenario of exploring local inherent structure minima as a basic feature of the fast dynamics of liquids, followed by "metabasin" transitions responsible for molecular diffusion to distances on the order of the interparticle distance at longer time scales accords with Heuer's hierarchical view of the dynamics of glass-forming liquids.…”
Section: Discussionmentioning
confidence: 59%
“…The slow process is observed in mechanical and dielectric relaxation processes, but it is not apparent in F(q 0 , t), explaining why we have said little about this relaxation process in the present paper. Cicerone and coworkers have suggested that the Johari-Goldstein relaxation process corresponds to transition events between metabasins in the potential energy landscape 91 and further that the rate of these transitions governs the rate of molecular diffusion. 92 This proposed interpretation of the Johari-Goldstein relaxation process, and the finding that t ⇤ scales inversely to the molecular diffusion coefficient in small molecule fluids, 37,[49][50][51][52] would suggest that t ⇤ might be identified with the Johari-Goldstein or slow -relaxation process.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion has recently also been derived for crystalline PCMs, where the propensity for local distortions leads to a very shallow energy landscape with different minima (58). While the origin of the complex landscape and its potential link to electron localization for amorphous PCMs are yet to be unraveled, the observation of -relaxation, which can be attributed to the barrier-crossing processes between neighboring minima as suggested by Stillinger and others (19,59) [or, alternatively, the metabasin transitions as suggested by a recent neutron scattering study (48)], is highly plausible.…”
Section: Discussionmentioning
confidence: 98%